2017
DOI: 10.22219/jpbi.v3i1.3888
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inquiry combined science-technology-society (STS) learning to enhance critical thinking skills on science

Abstract: One of the important skills to be mastered in the era of globalization is the critical thinking skills. This research is to determine the average increase of critical thinking skills of learners before and after implementing inquiry learning combined STS, and to know learner response about inquiry learning combined STS. This research was a “pre-experimental design” by design “the group pretest posttest design”. Samples were taken from the students of class VII SMPN 3 Peterongan. Data Collection was done by tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…There was research that uses only descriptive statistics or gain score as its data analysis technique (Aini & Budijastuti, 2017;Diwaluthfi, Ibrahim, & Fitrihidajati, 2017). On the other hand, there were also researchers who use paired sample t-test as a technique of data analysis (Jariyah, 2017;H. Rahmawati, Susantini, & Wisanti, 2017;Rifqiawati, Wahyuni, & Rahman, 2017).…”
Section: Percentage Of Each Research Subjectsmentioning
confidence: 99%
“…There was research that uses only descriptive statistics or gain score as its data analysis technique (Aini & Budijastuti, 2017;Diwaluthfi, Ibrahim, & Fitrihidajati, 2017). On the other hand, there were also researchers who use paired sample t-test as a technique of data analysis (Jariyah, 2017;H. Rahmawati, Susantini, & Wisanti, 2017;Rifqiawati, Wahyuni, & Rahman, 2017).…”
Section: Percentage Of Each Research Subjectsmentioning
confidence: 99%
“…These facts are in line with the research of Zaini and Jumirah (2016) which reported that a good learning media integrated with inquiry learning has contributed to the improvement of students' critical thinking skills, social skills, and work together. Similarly, several researches have implemented inquiry based learning to elevate students' critical thinking skills (Fahrurrizal et al, 2019;Thaiposri & Wannapiroon, 2015), either in basic or in combining forms such as combined with science-technology-society (Jariyah, 2017) and virtual laboratory media (Wahyuni & Atun, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Kegiatan pembelajaran yang didesain dimana peserta didik mengindentifikasi masalah akan mendorong peningkatan kemampuan berpikir kritis (Atmojo, 2009). Pembiasaan berpikir kritis menjadi penentu kemampuan dalam menjawab permasalahan pada saat mengikuti kegiatan pembelajaran (Ekawati, Susetyarini, Pantiwati, & Husamah, 2015;Jariyah, 2017). Aktivitas mengidentifikasi mendorong berpikir kritis karena menuntut kemampuan menganalisis suatu masalah.…”
Section: Peningkatan Keterampilan Berpikir Kritis Melalui Penerapan Munclassified